Efficacy and safety of anlotinib combined with immune checkpoint inhibitors and platinum-containing chemotherapy for later-line advanced non-small cell lung cancer: a retrospective three-arm real-world study using propensity-score matching - Wang, Zeyang; Ren, Bingnan; Yang, Haotian; Qiu, Xuejia; Wu, Yin; Xue, Chaojun; Zhao, Yue; Li, Xiao; Yu, Ze; Zhang, Jinyuan (Frontiers in Oncology, 2024)
ObjectiveTo assess the efficacy and safety of anlotinib combined with immune checkpoint inhibitors (ICIs) in patients with advanced non-small-cell lung cancer (NSCLC).MethodsClinical data on patients with advanced NSCLC were collected from June 2019 to October 2022 at Hebei General Hospital, China. The efficacy and safety of anlotinib combined with ICIs and platinum-containing chemotherapy were retrospectively analyzed. The primary endpoint was progression-free survival (PFS). The secondary endpoint was the disease control rate (DCR) and overall survival (OS). Survival curves were created using the Kaplan–Meier method. The efficacy and adverse reactions were evaluated according to the RECIST 1.1 and CTCAE 5.0 standards.ResultsA total of 54 patients were enrolled in this study after propensity score matching (PSM), including 27 men and 17 women, with a median age of 59. A total of 26 patients received anlotinib + ICIs + platinum-containing chemotherapy (AIC), 15 patients received anlotinib + platinum-containing chemotherapy (AC), and 13 patients received ICIs + platinum-containing chemotherapy (IC). The PFS of the AIC group was 7.76 months (95% CI: 3.71–NC). The DCR was 65.38%. The OS endpoint had not been reached, The AIC combination regimen group had a significantly longer PFS than the IC group (mPFS, 7.76 vs. 2.33 months, p=0.012, HR=0.23, 95% CI: 0.06–0.8). There was no significant difference in the DCR between the two groups (65.38% vs. 53.85%, p=0.326). There was a statistically significant difference in PFS between the AC group and the IC group (mPFS, 9.2 vs. 2.33 months, p=0.02, HR=0.14, 95% CI: 0.03–0.65). There was no significant difference in the DCR between the two groups (40% vs. 53.85%, p=0.445). The common adverse reactions of the combination of anti-angiogenic agents, ICIs, and platinum-containing chemotherapy were anemia (34.62%), allergic reactions (19.23%), thrombocytopenia (11.54%), gastrointestinal reactions (15.38%), and hepatobiliary disorders (11.54%). Most of them were manageable.ConclusionsAnlotinib combined with immune checkpoint inhibitors and platinum-containing chemotherapy regimens offers a good survival benefit for patients with advanced non-small-cell lung cancer who fail to respond to standard therapy. When both efficacy and safety are considered, a combination of anti-angiogenic agents, ICIs, and platinum-containing chemotherapy can be used as a choice for the treatment of advanced NSCLC.